Application of single venous approach under echocardiography without angiography in closure of Patent Ductus Arteriosus - Pan Xiong; Quan Chen; Yiwei He (Journal of Cardiothoracic Surgery)
Abstract Background The conventional arteriovenous approach closure of patent ductus arteriosus (PDA) may be associated with more complications, especially in young infants. The objective is to explore the feasibility and clinical efficacy of interventional closure of PDA through a single venous approach under echocardiography without angiography. Methods 112 patients (32 males and 80 females) with PDA closed by different methods in Suining Central Hospital were enrolled, including 60 cases (Group 1) with a single venous approach under echocardiography without angiography and 52 cases (Group 2) with the conventional arteriovenous approach. There were no significant differences in age and gender composition between the two groups. The success rate of operation, complete closure rate of 24 h, procedure time, X-ray fluoroscopic time, radiation dose, intraoperative contrast volume, preoperative and postoperative creatinine, preoperative and postoperative uric acid nitrogen, bed rest time, total hospital stay, and incidence of vascular complications were compared between the two groups. Results There were no significant differences in the success rate of operation (100% vs. 100%) and the complete closure rate of 24 h (100% vs. 100%) between the two groups (P > 0.05). In the single venous approach group, the procedure time was (50.05 ± 4.78 min vs. 57.69 ± 6.44 min), the X-ray fluoroscopy time was (7.30 ± 0.78 min vs. 10.23 ± 1.58 min), and the radiation dose was (79.57 ± 15.18mGy vs. 219.22 ± 34.60mGy), contrast volume (0mL vs. 62.22 ± 22.69 ml), bed rest time (4.03 ± 0.99 h vs. 12.25 ± 1.73 h), total hospital stay (3.30 ± 0.52 days vs. 3.39 ± 0.49 days) and the incidence of vascular complications (0% vs. 13.9%) were significantly lower than those in the traditional angiography group (P < 0.05). There were no significant changes in creatinine (51.86 ± 12.75 umol/L vs. 53.09 ± 10.27 umol/L) and urea nitrogen (4.84.81 ± 1.21 mmol vs. 4.98 ± 0.93 mmol/L) before and after operation in single venous group (P > 0.05). Compared with preoperative creatinine level (68.23 ± 8.66umol vs. 59.23 ± 22.12umol) and urea nitrogen level (5.98 ± 1.13 mmol/L vs. 5.16 ± 1.49 mmol/L) in the traditional angiography group after operation (24 h), they were significantly increased (P < 0.05). Conclusions Compared with the conventional arteriovenous approach, the single venous approach has the outstanding advantage of reducing vascular complications, contrast volume, radiation dose, and procedure time. Compared with the conventional arteriovenous approach, on the basis of obtaining the same efficacy, the PDA occlusion of the single venous approach under echocardiography without angiography has the outstanding advantages of simplified operation, less X-ray radiation, no contrast agent injury, short bed rest time, and fewer vascular complications. It is a green and safe surgical method worth promoting for PDA patients with suitable anatomical conditions.